2016
DOI: 10.1177/0192623315621191
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Hepatic Macrophages Aggravates Liver Lesions Induced in Rats by Thioacetamide (TAA)

Abstract: Hepatic macrophages play crucial roles in hepatotoxicity. We investigated immunophenotypes of macrophages in liver injury induced in rats by thioacetamide (TAA; 300 mg/kg, intraperitoneal) after hepatic macrophage depletion; hepatic macrophages were depleted by liposomal clodronate (CLD; 10 ml/kg, i.v.) one day before TAA injection. Samples were obtained on post-TAA injection days 0, 1, 2, 3, 5, and 7. TAA injection induced coagulation necrosis of hepatocytes on days 1 through 3 and subsequent reparative fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…TAA can interfere with protein synthesis and enzyme metabolism in the liver, which can lead to chronic liver injury (35,36). Previous studies have demonstrated that TAA could induce hepatic fibrosis in rats (37,38). In the current study, H&E and VG staining revealed a marked increase in the number of necrotic hepatocytes and infiltrating inflammatory cells, with a markedly increased deposition of collagen fibers in the TAA group, as well as liver fibrosis were directly observed.…”
Section: Discussionsupporting
confidence: 57%
“…TAA can interfere with protein synthesis and enzyme metabolism in the liver, which can lead to chronic liver injury (35,36). Previous studies have demonstrated that TAA could induce hepatic fibrosis in rats (37,38). In the current study, H&E and VG staining revealed a marked increase in the number of necrotic hepatocytes and infiltrating inflammatory cells, with a markedly increased deposition of collagen fibers in the TAA group, as well as liver fibrosis were directly observed.…”
Section: Discussionsupporting
confidence: 57%
“…Once ingested by macrophages, the clodronate causes damage to macrophages via apoptosis, resulting in their depletion/disappearance 42,43) . Hepatic macrophages in rats are easily depleted by an intravenous injection of liposome-encapsulated clodoronate 44,45) . CD163-expressing Kupffer cells are almost completely depleted for long term, indicative of the most sensitive for clodoronate treatment (Fig.…”
Section: -2 Influences On Depletion Of Hepatic Macrophages In Homeomentioning
confidence: 99%
“…To further determine the functions of macrophages in hepatotoxicity, hepatic macrophages were depleted by liposomal clodronate one day before a single administration of a sub-lethal dose of TAA 45) . In clodronate-treated rats, not only M1-macrophages expressing CD68 and MHC class II, but alsoM2-macrophages positive for CD163 and CD204 are markedly decreased.…”
Section: -5 Aggravated Lesion Of Taa-induced Acute Liver Injury Undmentioning
confidence: 99%
“…Moreover, acute toxicity has been observed when administering liposomal zoledronic acid, most likely caused by increased cytokine production [168,186]. Furthermore, the long-term effects of macrophage depletion have yet to be investigated, as there are indications that macrophage depletion may aggravate liver lesions in liver injury and impair skeletal muscle repair after muscle injury [187,188]. However, targeting macrophages seems to be a more effective strategy than identifying tumor specific antigens, as these may change over the course of tumor development and expression may vary between different groups of patients [189].…”
Section: Future Perspectivesmentioning
confidence: 99%